Solidification conditions of gray and white cast iron. Part II, Experimental verification - Fraś, Edward; Górny, Marcin; López, Hugo F. (My University, 2005)
In this work, an experimental verification of the theoretical principles for the transition from gray to mottled and white cast iron solidification is presented. Experimental tests have been implemen-ted using plate and wedge shaped castings of various sizes. The experiments included inoculated and non-inoculated cast irons of different chemical compositions and time after the inoculation treatment. In addition, thermal analysis tests were employed to determine the degree of undercooling of graphite eutectic ATm. This included microstructural evaluations in order to establish the density of eutectic grain (cells). This procedurę enabled the calculation of the theoretical grain density (celi count) TV, the wedge value w, as well as the chilling tendency CT of cast iron. It was found that the predictions of the theoretical analysis are in good agreement with the experimental outcome for the chill exhibited in wedge and plate shaped castings.

W pracy przedstawiono wyniki badań mających na celu doświadczalną weryfikację teoretycznego modelu przejścia od krystalizacji żeliwa szarego do połowicznego i białego. W badaniach doświadczalnych wykorzystano odlewy w kształcie płyt o zróżnicowanej grubości ścianki oraz odlewy w kształcie klina. Badaniami objęto żeliwo nie modyfikowane oraz modyfikowane, o różnym składzie chemicznym i różnym czasie po modyfikowaniu. Dodatkowo wykonano analizę termiczną żeliwa oraz badania struktury w celu określenia odpowiednio: stopnia przechłodzenia eutektyki grafitowej ATm oraz gęstości ziaren (komórek) eutektyki grafitowej. Zastosowana procedura pozwoliła obliczyć teoretyczną gęstość ziaren (liczbę komórek) TV, liczbę klinową w, a także skłonność żeliwa do zabieleń CT. Wykazano dobrą zgodność wyników obliczeń z danymi doświadczalnymi, które uzyskano dla odlewów w kształcie płyt i klinów.
Metallurgy and Foundry Engineering
Keywords: chill; chilling tendency; graphite eutectic; zabielenia; skłonność żeliwa do zabieleń; cementite eutectic; eulektyka grafitow; eulektyka cementytowa; cast iron; żeliwa